A Method of Product Stock Sharing Within SMEs Community Applied in E-commerce Platform - Jumail Wastam; Endang Rudiatin (Universitas Muhammadiyah Semarang Press, 2021)
The main problem of community empowerment in Small and Medium Enterprenership is the lack of an entrepreneurial ecosystem that helps SMEs adopt technology from larger businesses (R&D transfer), further there is high level enough of opportunity to do business in Indonesia, however the business sustainability is still low. Meanwhile, forming a business community will be one of the best alternatives to support in maintain business sustainability, where this can be achieved by collaboration in order to involve similar business units into a productive SMEs community. Developing SMEs community product share is an innovative method in this study so that product stock could remain available and it is mean business can continously productive. Developing business community of SMEs give an essential advantages to the target customers, where they are may face more stock of similar product from various store in one etalase. An e-commerce platform may facilitates this SMEs community for product share method. In this study has explore xpooz.id as a case which product share method are implemented and tested. Observational analysis, and questionnaire are conducted to have public and SMEs respond on the importance of product stock availability. The result of 98.4% participants has showing their positive responses on the case, 85.3% has shows how impact of the product stock availability, which is mean that the e-commerce platform have to give seriously consideration on community based product share stock as an important method.